Tax Payer Legal Compliance In Scoping Review - Dwi, Purwaningtyas; Agus, Suyoso; Nur, Taufik; Novita, Sari (Indonesian Journal of Law and Justice, 2025)
The purpose of this research is to systematically identify and analyze the development of studies on taxpayer legal compliance through a scoping review approach in the context of constitutional law. The research method uses a scoping review by examining scientific literature from various reliable sources over the past ten years. The finding indicate that the degree of taxpayer legal compliance is shaped not only by the clarity and effectiveness of regulatory instruments and law enforcement mechanisms but also by the extent of public confidence in government institutions. The conclusion emphasizes the importance of improving transparent and accountable state financial governance, strengthening the oversight mechanism for the use of the state budget, and optimizing tax law enforcement as an effort to build public trust and improve taxpayer legal compliance in a sustainable manner.